Engaging Minds: The Impact of Project-Based Learning in Junior High Education at SMPM 1 Surabaya - Rachmanetha, Dizzy Vreda (Universitas Muhammadiyah Surabaya, 2025)
This article examines project-based learning’s (PBL) transformative potential as a teaching method for junior high students at SMPM 1 Surabaya. By prioritizing active participation and teamwork, PBL enhances students’ critical thinking, problem-solving abilities, and motivation. The study reviews existing research, analyzes PBL’s implementation at SMPM 1 Surabaya, and discusses its influence on students’ academic performance and essential life skills. The findings reveal that PBL not only strengthens students’ academic achievements but also equips them with competencies required to meet future challenges.